2016
DOI: 10.1002/ets2.12118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Digital Information Literacy in Higher Education: A Review of Existing Frameworks and Assessments With Recommendations for Next‐Generation Assessment

Abstract: Digital information literacy (DIL)—generally defined as the ability to obtain, understand, evaluate, and use information in a variety of digital technology contexts—is a critically important skill deemed necessary for success in higher education as well as in the global networked economy. To determine whether college graduates possess the requisite knowledge and skills in DIL, higher education institutions must be able to administer and use results from valid assessments of DIL. In this paper, we provide a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 39 publications
1
49
0
6
Order By: Relevance
“…In this sense, it is vital that higher education institutions promote explicit and intentionally reasoned DL development strategies, monetising the competencies that, as users, students and teachers possess, but improving the competencies that allow them to develop criteria for the selection of relevant and pertinent information, respecting the scientific criteria of each area, and enhancing the digital competencies they possess (Sparks et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, it is vital that higher education institutions promote explicit and intentionally reasoned DL development strategies, monetising the competencies that, as users, students and teachers possess, but improving the competencies that allow them to develop criteria for the selection of relevant and pertinent information, respecting the scientific criteria of each area, and enhancing the digital competencies they possess (Sparks et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In higher education, besides the characteristics of the teachers, the educational system and the organisation itself, it should not be assumed that students necessarily have a high DL (Argelapós & Pifarré , 2017;Prior et al, 2016, Khalid & Pederson, 2016Sparks et al, 2016). Research reveals that there are different levels, for different motives and reasons.…”
Section: Essential Relationship Between the Development Of Digital LImentioning
confidence: 99%
“…Digital literacy frameworks differ in their emphasis on topics like civic engagement, identity, wellness, ethical or legal issues including copyright and privacy law, and the role of technical skills (Alexander et al, 2017;Hall et al, 2014;Sparks et al, 2016). For example, Hall et al found that few digital literacy frameworks identify online identity as its own area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, according to literature, it seems relevant to not start from the assumption that either teachers or students are necessarily digital literates; hence, the need arises to promote digital learning in higher education [46][47][48][49].…”
Section: Guidelines On How To Teachmentioning
confidence: 99%